Pride and prejudice - Austen, Jane (New York : Dover Pub., 2009)
Tale of pre-Victorian British country society in which Mrs. Bennett is faced with the task of marrying her five daughters, of whom the oldest, intelligent and witty Elizabeth, becomes involved with the proud sophisticate Mr. D'Arcy, before all ends well.
Dramatization by Helen Jerome ; music score, Herbert Stothart ; film editor, Robert J. Kern ; camera, Karl Freund ; art director, Cedric Gibbons ; gowns by Adrian.
New York times
Greer Garson, Laurence Olivier, Mary Boland, Edmund Gwenn, Edna May Oliver, Maureen O'Sullivan, Frieda Inescort, Edward Ashley.
Copyright Collection.
Turner Entertainment Co. Collection.
Keywords: Bennet, Elizabeth -- (Fictitious character) -- Drama; Courtship -- Great Britain -- Drama; Families -- Drama